New insight into the pathogenesis of insulin resistance in hyperthyroidism and hypothyroidism - Heba H El Demellawy; Mohamed A El Feky; Rania A Shoier; Olfat G Shaker (SpringerOpen, 2013)
Background and aim Thyroid hormones are linked to the different metabolic processes in the body.We evaluated the association of metabolic syndrome and different thyroid diseases. Patients and methods Eighty female patients were enrolled in this study; 40 hypothyroid (group I) and 40 hyperthyroid (group II) as well as 40 healthy females as control group. Waist circumference, BMI, fasting blood glucose, fasting insulin, HOMAIR index, adiponectin, free T3, freeT4, TSH, total cholesterol and HDL were measured in all patients. Results Adiponectin was lower in hypothyroid group (3.68 ± 0.63 ng/dl) and higher in hyperthyroid group (7.52 ± 0.68 ng/dl) than the control group (5.11 ± 0.67 ng/dl) P = 0.0001. The HOMAIR was higher in both hypothyroid (3.56 ± 0.57 ng/dl) and hyperthyroid groups (1.68 ± 0.27) compared to control group (1.33 ± 0.25) P = 0.0001. The cholesterol was also higher in both hypothyroid (161.22 ± 12.98 mg/dl) and hyperthyroid (147.02 ± 8.7 mg/dl) compared to control group (134.74 ± 6.34 mg/dl) P = 0.0001. The HDL was low in both hypothyroid group (35.86 ± 3.55 mg/dl) and hyperthyroid group (40.34 ± 3.17 mg/dl) compared with the control group (41.64 ± 3.12 mg/dl) P = 0.04. The adiponectin was positively correlated to free T3, free T4 and negatively correlated to TSH (r = 0.8, P = 0.0001; r = 0.9, P = 0.000; r = -0.9, P = 0.0001) respectively. HOMAIR was significantly correlated to the thyroid parameters (r = -0.8, P = 0.0001; r = -0.9, P = 0.0001; r = 0.8, P = 0.0001) respectively. The total cholesterol was negatively correlated with the free T3 and T4 (r = -0.5, P = 0.0001; r = -0.5, P = 0.0001) and positively correlated with the TSH (r = 0.5, P = 0.0001), It was also negatively correlated with adiponectin (r = -0.5, P = 0.0001), and positively correlated with HOMAIR (r = 0.5, P = 0.0001). The HDL was negatively correlated with TSH (r = -0.5, P = 0.000) and HOMAIR (r = -0.5, P = 0.0001), it was positively correlated with free T3, T4 (r = 0.6, P = 0.000; r = 0.5, P = 0.000) and adiponectin (r = 0.5, P = 0.0001). Conclusion Both hypo and hyperthyroidism were associated with insulin resistance and disturbances in lipid profiles.